(untitled) (Journal of Academic Research, 2023)
Objective: The aim of this survey was to evaluate the current trends in the practice of general dental practitioners regarding the root canal irrigation during endodontic treatment in private and governmental dental clinics in Misurata- Libya. Materials and Methods: A descriptive questionnaire survey was circulated among 220 general dental practitioners in private and governmental dental clinics in Misurata-Libya. The analysis of data was performed using SPSS. The descriptive statistics were used for determination of the frequency and percentage of the participant’s responses. Chi-Square test was used to assess the impact of work sector and professional experience on the responses (P < 0.05). Results: A total of 186 completed the survey questionnaire, giving a response rate of 84.5%. Around 99% of respondents used sodium hypochlorite in irrigation protocol while EDTA was included by 42%. 60% of respondents used full strength sodium hypochlorite (5.25%). 83.3% of respondents used smaller needle gauge (25 and 27). 68% of respondents used syringe capacity ˃5.0 ml. Only 45% of respondents used irrigation adjuncts and 89% agitate the irrigation solution manually. Around 38% of respondents insert the irrigation needle 2-3 mm from the apex. The majority of respondents irrigate the root canals ˂ 10 minutes and do not change their primary irrigation solution according to the pulpal or periapical status. No significant impact observed for either the working sector or professional experience on the responses. Conclusion: General dental practitioners in Misurata should be encouraged to introduce various techniques and adjuncts to improve the efficacy of endodontic irrigants.